Chaos in the Classroom: Center Learning in a 1st Grade Setting - Courtney F Lanaux; Kristen E Vice; Kenneth J Fashing-Varner (Networks: An Online Journal for Teacher Research, 2014)
How can centers be utilized in a classroom so students have full control of what they are learning and when? Can centers be used effectively post-kindergarten? During student teaching in a first grade classroom in southeast Louisiana, two student teachers, their classroom mentor teacher, and the 1st grade students experienced center learning that integrated all areas of the curriculum and was utilized for 45 minutes each day. Students were expected to determine which center they needed to attend each day, which activity to complete, who to complete it with, where to put completed work, and how to successfully tidy up the center. The classroom teacher used this independent exploratory learning time to pull students in small groups to target their reading and comprehension skills. The purpose of this research was to determine which factors played an integral part of the success of center learning in a first grade classroom. The student teachers observed the 16 centers, interviewed the students and the teacher, took photos, and videoed center time. After analyzing the research, centers appeared to be organized in an effective manner, student learning was the primary goal, which enhanced students’ ability to enjoy learning in centers and also gain social skills through collaboration.